Emerging Asias: Introduction. Issue 2 (2nd April 2016) - Sheppard, Eric
Abstract : This focus section explores what it means to think geographically about an emergent Asia. The four articles are based on presentations given at the Presidential Plenary session at the 2013 Association of American Geographers annual meeting in Los Angeles. In this Introduction, I briefly examine the temporalities associated with the term emergent and the spatialities evoked by the label Asia, arguing that mainstream conceptions of emergence, as progress into the light, and territorial conceptions of Asia require critical reflection from the perspective of contemporary geographical thought. These issues are taken up in the subsequent articles, examining when is Asia, the U.S. role in constructing representations of Asia, the Japanese origin of global supply chains, and the question of whether Western urban theory suffices to account for urbanization in China.